MODEL SYSTEM OF PETROCHEMICAL AND METALLOGENIC TRENDS OF GRANITOIDS AS A BASIS FOR THE PROGNOSIS OF SN, LI, TA, NB, W, MO, AND CU DEPOSITS - Borodin L.S. (My University, 2004)
A model system of classified petrochemical trends for granitoids with the main types of associated ore deposits (Sn, Li, Ta, Nb, W, Mo, and Cu) is presented. The model is based on generalized information on granitoids of many ore provinces in Russia and foreign countries (Transbaikalia, Kazakhstan, the Urals, Yakutia, the Russian Far East, the Erzgebirge, Central Massif Francais, western United States, Malaysia, Indonesia, Northern Nigeria, etc.). Attention was focused on concrete intrusive complexes accompanied by large ore deposits. For their standardization, an earlier elaborated method of trend analysis based on complex petrochemical parameters that govern the behavior of petrogenic and rare elements was used. The following standard trends were established for the main types of granitoids and associated ore deposits: (1) a Sn trend for calcalkaline granitoids of Sn-bearing provinces; (2) a Li-Ta-Sn trend for subalkaline peraluminous Li-F leucocratic granites (leucogranites) of rare metal-bearing provinces; (3) a W trend for subcalc-alkaline leucogranites of complex W-bearing provinces; (4) a Cu trend for low-alkaline subcalcareous mesogranites of Cu porphyry provinces; and (5) a Mo trend for monzonitoids and subcalc-alkaline granites and leucogranites of Mo porphyry provinces. On the basis of these trends and standard chemical-analytical information, classified criteria for distinguishing the main types of granitoid complexes promising for discovery of ore deposits, including the largest, were suggested.